Uso da medida de risco CVaR para estimação de retornos de fundos multimercados brasileiros - Santos, Ana Carolina Caetano dos (2019)
The Brazilian hedge funds industry has grown significantly in recent years. It is currently the second largest class of funds, second only to Fixed Income funds. Given the importance of this category, this dissertation aims to analyze the relationship between risk and return of hedge funds. For this, the Conditional Value at Risk is used as a measure of risk, a measure with valuable properties in relation to the traditional measures such as variance. The relationship between risk and return was verified through the creation of portfolios, such as those of Fama and French (1993), and regressions with panel data. The data contain information from 326 brazilian hedge funds from january 2010 to december 2017. It should be noted that hedge funds portfolios with higher CVaR (risk) have a low average return and high volatility, while lower risk portfolios have, on average, better performance and lower volatility. Analyzing the multimarket funds individually, through regressions with panel data, a direct relationship between risk and funds monthly return is observed. The size of funds seems to be indirectly related to active funds and direct related with closed funds. The age of the funds did not present a significant relationship with returns from hedge funds.